2020
DOI: 10.1097/mpa.0000000000001642
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Electrochemotherapy of the Pancreas in a Porcine Model

Abstract: Objectives The use of thermal ablative therapies in the pancreatic tumors is limited because of the risk of the vessel injury and potential pancreatitis or fistula formation. Electrochemotherapy (ECT) is an ablative therapy with an established role in the treatment of cutaneous and liver tumors. This study was designed to evaluate the safety and feasibility of ECT of the pancreas in a porcine survival model. Methods In the first group, 4 animals underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Formation of the aqueous pores in the lipid bilayer is the widely recognized mechanism, but evidence is growing that individual membrane lipids and proteins changes also contribute at ECT cytotoxic effect (61). The increased accumulation of intracellular drug concentration has actually been shown both in vitro and in vivo (58,(62)(63)(64)(65).…”
Section: Electrochemotherapymentioning
confidence: 99%
“…Formation of the aqueous pores in the lipid bilayer is the widely recognized mechanism, but evidence is growing that individual membrane lipids and proteins changes also contribute at ECT cytotoxic effect (61). The increased accumulation of intracellular drug concentration has actually been shown both in vitro and in vivo (58,(62)(63)(64)(65).…”
Section: Electrochemotherapymentioning
confidence: 99%
“…The pig is a common research model for translational medicine due to its anatomical and physiological resemblance to humans and was therefore selected for our research on the effects of electroporation (Djokic et al 2018;Campana et al 2019) on the pancreas (Dežman et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Its feasibility and safety were demonstrated in preclinical studies in porcine and rabbit models. 11 , 12 This was also confirmed in a few clinical studies demonstrating the feasibility and safety of the treatment in a palliative setting. 13 , 14 , 15 However, there is a lack of preclinical studies assessing the actions of different drugs used in ECT, their mechanisms and interactions with targeted drugs that are used in clinical practice.…”
Section: Discussionmentioning
confidence: 55%
“…The feasibility and safety of this approach was established in preclinical studies in a porcine and rabbit models, where it was demonstrated that ECT with bleomycin does not cause devastating complications such as acute pancreatitis, pancreatic fistula, or vascular injury. 11 , 12 The first clinical studies were also conducted, demonstrating the feasibility and safety of the treatment in a palliative setting. 13 , 14 , 15 However, there is a lack of preclinical studies assessing the actions of different drugs used in ECT, their mechanisms and interactions with targeted drugs, which are currently used in clinical practice for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%